Profil Sistem Usaha Pertanian Gambir di Sumatera Barat - Nasrul Hosen (Jurnal Penelitian Pertanian Terapan, 2017)
Gambier is thespecific commodity of West Sumatra. The research was aimed to find a description of gambier agribusiness, potential and constraint to improve and increase productivity and farmer income. This research on the profile of gambier agribusiness was done on March-October 2015 in Limapuluh and Pesisir Selatan District as the central produce of gambier in West Sumatra. The survey used for data collecting from 30 farmers and 10 merchants according to its level selected at random. Data were analyzed using descriptive, marketing system and economics analysis. The results showed that planted area of gambier increased but production have fluctuation from year to year. Cultivation technology of gambier very simple and without fertilizing. Productivity is 0.70 t/ha/yr. Gambier were exported to various state especially India, Pakistan and Singapore. Price and quality of gambier determined by the merchant. Nationally market compartment export gambier from West Sumatra more than 70.0%. The share of farmer price is 43.1% less than margin share about 56.9%, its mean marketing system inefficient. Profit of gambier is low because ofhight cost of processing, but still feasible with B/C=1.53. Suggest to policy maker and farmer to: (i) Push the growing micro and small industry to produce secondary product of gambier; (ii) Improve of subsystem produce through applying of innovation, development of appliance simple innovation to processe of gambier; (iii) Farmer group alliance institution (gapoktan) pushed to grow marketing unit and warehouse scrip certificate system by exploiting fund in Micro Financial Institution of Agribusiness (MFI-A) and village funds. Expected, for next time the farmer does not depend on raw material exporting of gambier. Keywords: export, marketing, micro industry, productivity, profit, gambier